Loss of desiccation tolerance in Copaifera langsdorffii Desf. seeds during germination - Pereira, Wilson Vicente Souza; Faria, José Marcio Rocha; Tonetti, Olivia Alvina Oliveira; Silva, Edvaldo Aparecido Amaral da [UNESP] (Int Inst Ecology, 2014)
This study evaluated the loss of desiccation tolerance in C. langsdorffii seeds during the germination process. Seeds were imbibed for 24, 48, 72, 96, 120 and 144 hours and dried to the initial moisture content, kept in this state for 3 days after which they were submitted to pre-humidification and rehydration. Ultraestructural evaluations were done aiming to observe the cell damage caused by the dry process. Desiccation tolerance was evaluated in terms of the percentage of normal seedlings. Seeds not submitted to the drying process presented 61% of normal seedlings, and after 24 hours of imbibition, followed by drying, the seeds presented the same percentage of survival. However, after 48 hours of imbibition, seeds started to lose the desiccation tolerance. There was twenty six percent of normal seedlings formed from seeds imbibed for 96 hours and later dried and rehydrated. Only 5% of seeds imbibed for 144 hours, dried and rehydrated formed normal seedlings. At 144 hours of imbibition followed the dry process, there was damage into the cell structure, indicating that the seeds were unable to keep the cell structure during the drying process. Copaifera langsdorffii seeds loses the desiccation tolerance at the start of Phase 2 of imbibition.

Este estudo avaliou a perda da tolerância à dessecação em sementes de C. langsdorffii durante o processo germinativo. Sementes foram embebidas por 24, 48, 72, 96, 120 e 144 horas e depois secas até a umidade inicial, sendo mantidas neste estado durante 3 dias, quando então foram submetidas a pré-umidificação e reidratação. Avaliações ultraestruturais foram realizadas objetivando observar danos nas células causados pelo processo de secagem. A tolerância à dessecação foi avaliada pelo percentual de plântulas normais. Sementes não submetidas ao processo de secagem apresentaram 61% de plântulas normais, sendo que após 24 horas de embebição seguida de secagem, houve o mesmo percentual de sobrevivência. Contudo, após 48 horas de embebição, as sementes começaram a perder a tolerância à dessecação. Vinte e seis por cento de sementes formaram plântulas normais após embeberem por 96 horas e secas. Apenas 5% de sementes embebidas por 144 horas e secas formaram plântulas normais. Após 144 horas de embebição, seguida de secagem, verificou-se danos na estrutura celular, o que indica que as sementes não são capazes de manter a estrutura celular durante o processo de secagem. Verificou-se no presente estudo que sementes de C. langsdorffii perdem a tolerância à dessecação no inicio da fase 2 da embebição.
Perda da tolerância à dessecação em sementes de Copaifera langsdorffii durante a germinação
Keywords: Copaiba; Desiccation sensitivity; Imbibition; Copaíba; Sensibilidade à dessecação; Embebição